Mechanosynthesis, Crystal Structure and Magnetic Characterization of Neodymium Orthoferrite - Pedro Vera Serna; Cecilio García Campos; Felix Sánchez De Jesús; Ana María Bolarín Miró; José Antonio Juanico Lorán; Jeffrey Longwell (Materials Research, 2016)
Neodymium orthoferrite NdFeO3 was obtained at room temperature by mechanosynthesis with a stoichiometric ratio of Nd2O3 and Fe2O3 powders, whereas the traditional synthesis requires a temperature of approximately 1000 °C. The crystal structure was analyzed by X-ray diffraction analysis using Cu radiation and a LynxEye XE detector, whose strong fluorescence filtering enabled a high signal intensity. The analysis indicated that the obtained crystallites were nano-sized. The particle morphology was observed by scanning electron microscopy, and the magnetic saturation was tested by vibrating sample magnetometry. The synthesis of NdFeO3 was detected after a few hours of milling, indicating that the milling imparted mechanical energy to the system.